1990
DOI: 10.1007/bf00308714
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy with altered mitochondria due to a triosephosphate isomerase (TPI) deficiency

Abstract: Morphological changes are shown in the muscle biopsy specimens of an 8-year-old girl who suffered from a triosephosphate isomerase (TPI) deficiency, resulting in a chronic, nonspherocytic, hemolytic anemia, mental retardation and neuromuscular impairment. The newly introduced enzyme histochemical reaction for TPI demonstrated a total lack of histochemically detectable enzyme activity, whereas biochemical analysis of muscle tissue revealed less than 10% of the normal enzyme activity. Electron microscopy showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Specifically, phosophocreatine was not reduced in sgk mutants but was surprisingly found to be significantly increased, possibly resulting from reduced animal activity ( Figure 6). Also, sgk 1 mutants do not have aberrant mitochondrial ultrastructure ( Figure 5) as observed in another stress-sensitive fly mutant (Celotto et al 2006) and suggested by previous studies using human tissues (Bardosi et al 1990). Lactic acid levels were found to be decreased, suggesting a reduction in the overall rate of glycolysis, but this does not result in a depletion of phosphocreatine levels that would be consistent with bioenergetic impairment (Figure 6).…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, phosophocreatine was not reduced in sgk mutants but was surprisingly found to be significantly increased, possibly resulting from reduced animal activity ( Figure 6). Also, sgk 1 mutants do not have aberrant mitochondrial ultrastructure ( Figure 5) as observed in another stress-sensitive fly mutant (Celotto et al 2006) and suggested by previous studies using human tissues (Bardosi et al 1990). Lactic acid levels were found to be decreased, suggesting a reduction in the overall rate of glycolysis, but this does not result in a depletion of phosphocreatine levels that would be consistent with bioenergetic impairment (Figure 6).…”
Section: Discussionsupporting
confidence: 76%
“…The amino acid Val at 231 position is conserved from bacteria to man, is known to be involved in substrate binding, and is predicted to significantly alter catalytic activity (8). The Val231Met mutation is associated with decreased isomerase activity, increase in intracellular glycogen, and mitochondrial changes similar to those seen in mitochondrial myopathies (26,27).…”
Section: Tpi Mutations: Structure and Functionmentioning
confidence: 99%
“…Two variants (Cys41Tyr and Val231Met) were classified as "pathological (intermediate)" as they exhibited many of the stereotypical clinical phenotypes of TPI deficiency including haemolytic anaemia and neuromuscular impairment but patients with these variants survived longer than the typical TPI deficiency patient. In contrast to the more severe TPI deficiency cases, three of these patients were eight years of age and one was aged 15 at the time their cases were described in the literature (Arya et al, 1997;Bardosi et al, 1990;Orosz et al, 2006;Serdaroglu et al, 2011;Wilmshurst et al, 2004).…”
Section: Tpi Deficiency Variants Can Be Arranged Into Four Groups Depmentioning
confidence: 91%